One‐Pot Hydrothermal Synthesis of Ternary 1T‐MoS2/Hexa‐WO3/Graphene Composites for High‐Performance Supercapacitors. Issue 70 (19th November 2019) - Naz, Raheela; Liu, Qinglei; Abbas, Waseem; Imtiaz, Muhammad; Zada, Imran; Ahmad, Javed; Li, Tengfei; Gu, Jiajun
Abstract: A new ternary composite of 1T‐molybdenum disulfide, hexagonal tungsten trioxide, and reduced graphene oxide (M‐W‐rGO) is synthesized by using a one‐pot hydrothermal process. The synergetic effect of 1T‐MoS2 and hexa‐WO3 nanoflowers improves the electrochemical performance for supercapacitors by inducing additional active sites and hexagonal tunnels, respectively, which lead to high storage capacity and easy transfer of electrolyte ions. The ternary M‐W‐rGO composite has a high specific capacitance of 836 F g −1 at 1 A g −1, which is nearly twice that of binary composites of M‐rGO and W‐rGO with high capacitance retention of 86.35 % after 3000 cycles at a high current density of 5 A g −1 . This study provides a new ternary composite that can be used as an electrode material for high‐performance supercapacitors. Abstract : The flower of supercapacitors : 1T‐MoS2 and hexa‐WO3 nanoflowers are grown on a 3D network of reduced graphene oxide by using a one‐pot hydrothermal process. The hexagonal tunnel structure of WO3 and 1T conducting phase of MoS2 provide additional active sites, high storage capacity, and easy electronic transportation for high‐performance supercapacitor applications.